Evaluation of drug-induced neurotoxicity based on metabolomics, proteomics and electrical activity measurements in complementary CNS in vitro models. Issue 1 (25th December 2015) - Schultz, Luise; Zurich, Marie-Gabrielle; Culot, Maxime; da Costa, Anaelle; Landry, Christophe; Bellwon, Patricia; Kristl, Theresa; Hörmann, Katrin; Ruzek, Silke; Aiche, Stephan; Reinert, Knut; Bielow, Chris; et al.
Highlights: Free brain ratios of a drug are predicted by an in vitro blood brain barrier studies. Electrical activity measurements can classify drugs into neurotoxic or neuroactive. Changes in metabolites and proteins are potential biomarkers of neurotoxicity. An in vitro integrated testing strategy is proposed for neurotoxicity testing. Abstract: The present study was performed in an attempt to develop an in vitro integrated testing strategy (ITS) to evaluate drug-induced neurotoxicity. A number of endpoints were analyzed using two complementary brain cell culture models and an in vitro blood–brain barrier (BBB) model after single and repeated exposure treatments with selected drugs that covered the major biological, pharmacological and neuro-toxicological responses. Furthermore, four drugs (diazepam, cyclosporine A, chlorpromazine and amiodarone) were tested more in depth as representatives of different classes of neurotoxicants, inducing toxicity through different pathways of toxicity. The developed in vitro BBB model allowed detection of toxic effects at the level of BBB and evaluation of drug transport through the barrier for predicting free brain concentrations of the studied drugs. The measurement of neuronal electrical activity was found to be a sensitive tool to predict the neuroactivity and neurotoxicity of drugs after acute exposure. The histotypic 3D re-aggregating brain cell cultures, containing all brain cell types, were found to be well suited for OMICs analyses after both acute and long term treatment. The obtained data suggest that an in vitro ITS based on the information obtained from BBB studies and combined with metabolomics, proteomics and neuronal electrical activity measurements performed in stable in vitro neuronal cell culture systems, has high potential to improve current in vitro drug-induced neurotoxicity evaluation.